PENCIPTAAN CITY BRANDING MELALUI MASKOT SEBAGAI UPAYA MEMPROMOSIKAN KABUPATEN LUMAJANG - Lauwrentius, Stephen; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Various fields looked brand from their respective perspectives, including business and finance, marketing, advertising, sales, promotion, public relation, communication, graphic design, semiotics, psychology, statistics, anthropology, sociology, and others. While in the general population, are popular brand is considered as a logo, trademark, or the name of the entity. All purely physical. When in fact the brand is more of a summary of the experience and the Association against an entity, so much deeper than just the physical. While branding is an activity to build a brand. Identity, including logo, is one of the activities of the branding. Building a brand is a city meant to build the identity of the city. Identity, imagery, and communication is a three (3) important component in brand city. But for this brand gives more city spaces both to image or communication in the framework of the formation of the image. The mascot is capable of bridging the gap between brand with the target audience. Lumajang is one of the regions with rich natural potential is tremendous. Its natural beauty makes the Malang as one of the areas with the best natural beauty on the island of Java. Many natural beauties sucking tourists, not only local but also foreign misatawan. The County is becoming more and more interesting with a wealth of cultural tours and religinya. To this end the creation of the mascot is expected to introduce about Lumajang and promoting potential of Lumajang.Â Keywords: City Branding, Mascot, Media Promotions,Tours